The hidden victims: Civilian casualties of the two world wars - O` Grada, Cormac (Princeton Princeton University Press, 2024)
The Hidden Victims is the first book to attempt to measure and describe the full scale of civilian deaths during the world wars, from all causes, including genocide, starvation, aerial bombardment, and disease. While nations went to great lengths to record military casualties, they often didn$1 (Bt count or deliberately obscured civilian deaths. Getting the numbers right is important.s